2017
DOI: 10.3389/fevo.2017.00163
|View full text |Cite
|
Sign up to set email alerts
|

Urban Great Tits (Parus major) Show Higher Distress Calling and Pecking Rates than Rural Birds across Europe

Abstract: Environmental change associated with urbanization is considered one of the major threats to biodiversity. Some species nevertheless seem to thrive in the urban areas, probably associated with selection for phenotypes that match urban habitats. Previous research defined different "copying styles" in distress behavior during the handling of birds. These behaviors vary along a continuum from "proactive" to "reactive" copers. By studying avian distress behaviors we aimed to broaden our understanding of the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 84 publications
(140 reference statements)
3
28
0
1
Order By: Relevance
“…Previous research has shown that species usually show no or limited responses to anthropogenic disturbance (Bonier, 2012;Chavezzichinelli et al, 2010;Hudin et al, 2018;Sepp et al, 2018). In line with these results, the pace-of-life hypothesis predicts no differences in stress responses between urban and rural habitats (Sepp et al, 2018), but previous studies have been inconsistent in confirming this point with regard to BR variation, a proxy of acute stress responses to handling (Charmantier et al, 2017;Senar et al, 2017;Torné-Noguera et al, 2014). Our results, using hundreds of individuals from over a hundred species of passerines, demonstrate that there were no differences in BR, both between and within species, among natural, rural, and urban locations.…”
Section: Br Of Tropical Passerines Support the Pace-oflife Hypothesismentioning
confidence: 54%
See 1 more Smart Citation
“…Previous research has shown that species usually show no or limited responses to anthropogenic disturbance (Bonier, 2012;Chavezzichinelli et al, 2010;Hudin et al, 2018;Sepp et al, 2018). In line with these results, the pace-of-life hypothesis predicts no differences in stress responses between urban and rural habitats (Sepp et al, 2018), but previous studies have been inconsistent in confirming this point with regard to BR variation, a proxy of acute stress responses to handling (Charmantier et al, 2017;Senar et al, 2017;Torné-Noguera et al, 2014). Our results, using hundreds of individuals from over a hundred species of passerines, demonstrate that there were no differences in BR, both between and within species, among natural, rural, and urban locations.…”
Section: Br Of Tropical Passerines Support the Pace-oflife Hypothesismentioning
confidence: 54%
“…Previous research has shown inconsistent results when assessing changes in BR in response to urbanization, with different studies showing increased BR toward more urbanized areas (Charmantier, Demeyrier, Lambrechts, Perret, & Grégoire, ; Torné‐Noguera, Pagani‐Núñez, & Senar, ) or no significant differences in stress responses to handling between rural and urban birds (Senar et al., ). However, this evidence is limited to a single species (great tits Parus major ) and to a limited geographic region (SW Europe).…”
Section: Introductionmentioning
confidence: 99%
“…These findings reinforce the previous idea on the importance of cognitive and behavioural changes as key responses to urbanisation in birds and in particular in great tits. Indeed, song structure and escape or distress behaviour have been previously shown to differ between urban and rural great tit populations across Europe (Senar et al 2017;Slabbekoorn and den Boer-Visser 2006;Møller and Ibáñez-Álamo 2012). Nonetheless, whether this is the result of a genetic response to selection or phenotypic plasticity is to a large extent still unknown.…”
Section: Convergent Evolution Of Gene Functions In Response To Urbanimentioning
confidence: 99%
“…2016 ), behavioral ecotypes ( Charmantier et al. 2017 ; Senar et al. 2017 ), plumage coloration ( Isaksson et al.…”
Section: Introductionmentioning
confidence: 99%